Prospective, longitudinal study to isolate the impacts of marijuana use on neurocognitive functioning in adolescents - Ren, Wen; Fishbein, Diana (Frontiers in Psychiatry, 2023)
Policies to legalize possession and use of marijuana have been increasingly supported across the United States. Although there are restrictions on use in minors, many substance abuse scientists anticipate that these policy changes may alter use patterns among adolescents due to its wider availability and a softening of beliefs about its potentially harmful consequences. Despite the possibility that these policies may increase the prevalence of use among adolescents, the effects of marijuana on neurodevelopment remain unclear, clouding arguments in favor of or opposition to these policies. The present prospective, longitudinal study was designed to isolate the neurodevelopmental consequences of marijuana use from its precursors during adolescence—a period of heightened vulnerability for both substance use and disrupted development due to environmental insults. Early adolescents who were substance-naïve at baseline (N=529, aged 10-12) were recruited and tracked into adolescence when a subgroup initiated marijuana use during one of three subsequent waves of data collection, approximately 18 months apart. Results suggest that marijuana use may be specifically related to a decline in verbal learning ability in the short term and in emotion recognition, attention, and inhibition in the longer-term. These preliminary findings suggest that marijuana use has potential to adversely impact vulnerable neurodevelopmental processes during adolescence. Intensive additional investigation is recommended given that state-level policies regulating marijuana use and possession are rapidly shifting in the absence of good scientific information.